Hemorragia del tercer trimestre por Acretismo Placentario. - Martínez Suarez, Alexandra Arelis (2020)
Obstetric hemorrhage that occurs in the third trimester of pregnancy is associated with greater morbidity / mortality of the mother and fetus, pregnancy beyond the age of 30 years, the increase in the frequency of cesarean births, can increase the incidence of pathologies related to obstetric hemorrhage, adequate prenatal control and the performance of antepartum diagnosis through the use of gray scale ultrasound, color Doppler, power Doppler and Nuclear Magnetic Resonance is an insurmountable opportunity that allows us an adequate surgical planning of the delivery and the eventual need for a hysterectomy and / or blood transfusion, when determining placental accreta. This research shows the case of a 30-year-old 11-month-old patient with 37 weeks of gestation with insufficient prenatal controls who presents transvaginal bleeding of approximately 45 minutes with apparent physical effort as an apparent cause, arrives at the general hospital through the emergency area where an assessment is received By a gynecology specialist, speculoscopy is performed to determine the origin and amount of bleeding, there are no alterations in the product, there is no uterine dynamics, an obstetric ultrasound is performed where the placenta previa is evidenced, she is operated on in an emergency, obtaining a single live product without complications When cleaning the uterine cavity, areas of placental accreta were evident, so it was decided to perform a hysterectomy with preservation of the attachments, during the intraoperative period, she presented bleeding of approximately 1000 ml, so she was transfused 2 units of blood products, she remained hospitalized for 3 days. stay in control In his general state, he is discharged with a satisfactory evolution.